2006
DOI: 10.1007/s10531-005-5436-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of local knowledge in determining shade composition of multistrata coffee systems in Chiapas, Mexico

Abstract: This research explores interactions between farmers' knowledge and socioeconomic circumstances and the floristic composition of multistrata coffee plantations in Chiapas, Mexico. Interviews with 24 individual farmers with accompanying vegetation transects and two community level participatory workshops were carried out. The frequency, density, dominance, utility and importance value for all tree species surveyed were obtained. Farmers were grouped by cluster analysis on the basis of their land area, time produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 26 publications
5
37
0
10
Order By: Relevance
“…Our results are congruent with other studies that have found that the main criteria for tolerating, promoting, or planting shade trees include compatibility with crop, shade production, ease of management, production of organic matter, and production of valuable goods such as food, timber, firewood, and medicinal resources (Albertin and Nair 2004, Soto-Pinto et al 2007, Souza et al 2010, Anglaaere et al 2011. Farmers' knowledge of tree-crop interactions is fairly consistent with findings on the advantageous and disadvantageous ecological interactions between shade trees and crops (see Beer 1987, Beer et al 1997.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are congruent with other studies that have found that the main criteria for tolerating, promoting, or planting shade trees include compatibility with crop, shade production, ease of management, production of organic matter, and production of valuable goods such as food, timber, firewood, and medicinal resources (Albertin and Nair 2004, Soto-Pinto et al 2007, Souza et al 2010, Anglaaere et al 2011. Farmers' knowledge of tree-crop interactions is fairly consistent with findings on the advantageous and disadvantageous ecological interactions between shade trees and crops (see Beer 1987, Beer et al 1997.…”
Section: Discussionsupporting
confidence: 90%
“…Apparently, different species at each site perform the same function of carbon accumulation and carbon stocks depending more on tree and sapling density, wood density, tree management, and soil management (Palm, 1995;De Jong et al, 1997;Van Noordwijk et al, 2002;Montagnini & Nair, 2004;Chave et al, 2005;Soto-Pinto et al, 2007;Häger, 2012). Nevertheless, the ability of coffee systems to provide other ecosystem services, such as biodiversity conservation, erosion control, and pollination, is closely related to its complexity and diversity (Somarriba et al, 2004;Srivastava & Vellend, 2005;Perfecto et al, 2007;Philpott et al, 2008a;Vergara & Badano, 2009;Tscharntke et al, 2005Tscharntke et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Local knowledge is, as opposed to indigenous knowledge, not geographically or ethnically specific and can be similar at different locations if within similar agroecological context (Sinclair and Joshi 2000). While Albertin and Nair (2004) and Soto-Pinto et al (2007) have reported on local knowledge on tree diversity in coffee AFS, it is only in recent years that research has documented on both local knowledge and ES provision in coffee AFS and landscapes (Cerdán et al 2012;Lamond et al 2016;Smith-Dumont et al in press).…”
Section: Introductionmentioning
confidence: 99%